W obronie diety naturalnej - SHELLEY, Percy B.; CHABRAJSKA, Dorota (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2022)
Przekład eseju Percy’ego B. Shelleya A Vindication of Natural Diet: Being One in a Series of Notes to “Queen Mab”(a Philosophical Poem). Podstawa przekładu: Percy Bysshe Shelley, A Vindication of Natural Diet: Being One in a Series of Notes to “Queen Mab” (a Philosophical Poem), London and Manchester: F. Pitman, John Heywood and Offices of the Vegetarian Society, 1884.